Factors influencing employee’s job performance a study of SEDC headquarters, Kuching / Helmi Kamil - Kamil, Helmi (2012)
This research study represents a research about “Factors Influencing Employee’s Job Performance, A Study of SEDC Headquarters, Kuching”. Employee’s job performance influences organization competitiveness whether being more competitive or not in the market. This study would analyse on (1) the factors that is crucial in determining employee’s job performance at SEDC Headquarters, Kuching. (2) which factor have the strongest influence on employee’s job performance at SEDC Headquarters, Kuching and (3) which demographic factors have the strongest influence on employee’s job performance at SEDC Headquarters, Kuching. A sample of 77 staff from SEDC was being respondents and the result from the respondents gathered, analysed and presented in desiccative methods.